Melanoma arising in a giant nevus spilus maculosus - Alexander Stella; Katharina Ponholzer; Jessika Weingast; Michael Binder (Mattioli1885, 2011)
Melanoma arising in a nevus spilus is rare. There are two distinct types of nevus spilus characterized by macular or papular speckles, respectively. We report the case of a melanoma that arose in association with a giant nevus spilus maculosus.